Gamma Radiation Induced Changes in the Biochemical Composition of Aquatic Primary Producers and Their Effect on Grazers - Golz, Anna-Lea; Bradshaw, Clare (Frontiers in Environmental Science, 2019)
Changes in the biochemical composition of primary producers can alter their food quality, influencing their consumers and further propagating through the food web. Gamma (ɤ) radiation is an environmentally important type of ionizing radiation as it can damage macromolecules such as DNA, proteins, and lipids due to its high frequency, short wavelength, and high energy photons. Here, we investigate whether short-term ɤ-radiation changes the biochemical composition of primary producers and if radiation-induced changes affect higher trophic levels. Two phytoplankton species were exposed to two doses of ɤ-radiation and compared to a control. The metabolic profile and total protein content of the algae were measured at five time points within 24 h. Additionally, we measured carbon incorporation rates of Daphnia magna fed with the exposed algae. Gamma radiation had a significant effect on phytoplankton biochemical composition, although these effects were species-specific. The changes in phytoplankton biochemical composition indicate that ɤ-radiation induced the production of reactive oxygen species (ROS). D. magna incorporated more carbon when fed with algae previously exposed to ɤ-radiation; this could be due to radiation-induced changes in nutritional quality, algal anti-grazing defenses, or chemical feeding stimuli.